Retail investors and sustainable finance: exploring ESG investment preferences on Robinhood - Hofseth, Maren Ringen (2024)
This thesis explores the interest of retail investors in sustainable investments, explicitly focusing on ESG-rated stocks traded on Robinhood. By combining historical user data from Robinhood with ESG ratings, the study analyzes whether retail investors exhibit significant activity changes following these ratings' shifts. The research aims to determine if Robinhood users are responsive to sustainability metrics by examining their behavioral patterns after negative changes in ESG ratings. Through this analysis, the study seeks to provide insights into whether retail investors in Robinhood react to declines in ESG ratings or if they remain indifferent to such changes.